1973
DOI: 10.3177/jnsv.19.277
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Weight Gain and Free Amino Acid Concentration of Plasma and Liver in Rats Fed a Diet Supplemented With Various Amounts of Lysine

Abstract: This study was conducted to determine the effect of feeding graded levels of dietary lysine on weight gain and free amino acid concentra tions in blood plasma and liver of weanling rats. Animals were fed on diets containing 11.6% wheat gluten (equivalent in nitrogen to a 10% casein diet) supplemented with graded levels of L-lysine HCl (0 to 10%) for 14 days. An outline of the results obtained follows: 1) Maximum weight gain was observed with the groups fed the lysine supplement in the 0.64 to 1.8% range. Growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1973
1973
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…Furthermore, the supplement of lysine to the excess arginine diet tended to result in increases of arginine and lysine levels in plasma. The decline of plasma threonine concentration in animals fed diets supplemented with lysine was consistent with the results of previous observa tions (6,8 Table 2. Liver arginase activities in rats fed the basal (11.6% wheat gluten), basal plus 0.6% lysine• HCI, basal plus 5.0% arginine• HCI, and basal plus 5.0% arginine• HCl plus 0.6% lysine• HCl diets, respectively.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the supplement of lysine to the excess arginine diet tended to result in increases of arginine and lysine levels in plasma. The decline of plasma threonine concentration in animals fed diets supplemented with lysine was consistent with the results of previous observa tions (6,8 Table 2. Liver arginase activities in rats fed the basal (11.6% wheat gluten), basal plus 0.6% lysine• HCI, basal plus 5.0% arginine• HCI, and basal plus 5.0% arginine• HCl plus 0.6% lysine• HCl diets, respectively.…”
Section: Methodssupporting
confidence: 91%
“…Vitamin A (2,000 IU) and D2 (200 IU) were also added.4 Additions of 5.0% of single L-arginine• HCI, L-tryptophan, L-phenylalanine, L-methionine and L-tyrosine, with or without 0.6% of L-lysine• HCL were made at the expense of a-starch. This supplemental level of lysine to the basal diet was adequate for the requirement of lysine (6). When the experimental diet containing 5.0 arginine• HCl was prepared, 2.0% of sodium bicarbonate was included at the replacement of cellulose powder.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, a relationship between increasing dietary lysine and plasma threonine levels has been observed. An inverse relationship between dietary lysine level and plasma threonine has been reported by Muramatsu et al (1973) and Woerman and Speer (1976). Yamashita et al (1967) found that elevated levels of dietary lysine in creased liver threonine dehydratase activity.…”
Section: Death Lossmentioning
confidence: 97%
“…In both the fasting and postfeeding plasma samples, ment is beginning to be met (Muramatsu et al, 1973)• The lysine^threonine ratio approached and surpassed unity be tween 0.30 and 0.4l^ lysine in this experiment (Table 1). …”
Section: Lactationmentioning
confidence: 99%
“…Morrison et al (1961) Muramatsu et al (1973) found that plasma lysine increased well before the point of maximum grovrth with rats. Mitchell et al (1968), Stockland et al (1970) and Lewis and Speer (1974) determined that the plasma amino acid response involved two linear mathematical functions, when the data ware plotted on a graph, the intercept of the two functions was found to be very close to the amino acid requirement of the animal.…”
Section: The Influence Of Pregnancy and Nutrition On Nitrogen Metabolismmentioning
confidence: 99%